البعد الواقعي في فقه التّغيير على ضوء المنهج النّبوي - بلعمري, أكرم (University of Eloued جامعة الوادي, 2018)
يهدف هذا الموضوع إلى دراسة مظاهر الواقعية في سيرة النّبي صلى الله عليه وسلم، وقد تمّت معالجة الموضوع من خلال التّعريف بالواقعية وبيان حضورها في الممارسة النّبوية، من خلال منطق السّنة العملي وأثره في فقه الواقع، وقد برزت مظاهر الواقعية في منهج النّبي  في الدّعوة من خلال معرفته بأحوال النّاس عموما، ومراعاة ذلك في الفتوى، وتجلّى هذا البعد في المرونة في حلّ الأزمات المختلفة، وبرز أيضا في الفعالية في توظيف الكفاءات، واعتماد منهح التّدرج في التّغيير، سواء من خلال مرحلية الدّعوة أو التّشريع. Abstract The present topic aims at studying the aspects of realism in the biography of the Prophet Mohamed-peace and mercy be upon him. The topic has been studied through defining realism, then showing its presence in the sunnah of the prophet Mohamed-peace and mercy be upon him. The aspects of realism emerged in the approach of the prophet in the call (Daawa) through his knowledge of people’s problems, especially when he answers questions, or when he finds a solution to the various crises. These aspects appeared also in the use of the competences in important and difficult responsibilities, and the adoption of the gradient rule in everything, whether the legislation or the call (Daawa
The realistic dimension in the fiqh of change in light of The Prophetic Method
مجلة البحوث والدراسات المجلد 15 العدد02 جامعة الوادي
Keywords: الواقعية ؛ التغيير ؛ المنهج، النبوة; The real dimension, The Prophetic Method, the biography of the Prophet